Multikultural Adalah Kehendak Allah - Anhari, Anhari (ILJ: Islamic Learning Journal, 2025)
This study aims to explore the Islamic creed (aqidah) in understanding iradah (Allah's will) in relation to sunnatullah (Allah's decree), particularly regarding the inherently multicultural nature of human life. This research is crucial to ensure that Muslims, in particular, do not fall into "confusion" about why Allah creates diversity on one hand, while on the other, He teaches that Islam is the true religion in His sight. Another objective of this study is to examine how the Ahlussunnah wal Jama’ah creed, as the group considered most correct, applies its approach to understanding multiculturalism.